2019
DOI: 10.1111/1749-4877.12312
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and the brain of brood parasitic cowbirds

Abstract: Cowbirds are brood parasites. Females lay their eggs in the nests of other species which then incubate the cowbird eggs and raise the young cowbirds. Finding and returning to heterospecific nests presents cowbirds with a number of cognitive challenges. In some species, such as brown-headed cowbirds (Molothrus ater), females but not males, search for and remember the locations of potential host nests. We describe recent research on sex differences in cognition and the hippocampus associated with this sex differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…For example, a current focus of research in food caching species is to measure spatial learning under standardised conditions, usually on a small scale, to infer performance in cache retrieval at a larger spatial scale, or to predict fitness, but it remains unclear whether observed associations relate to navigation through the environment or cache retrieval at a fine spatial scale (Healy, 2019;Healy et al, 2005Healy et al, , 2009Krebs et al, 1990;McGregor & Healy, 1999). Similarly, work on parasitic cowbirds in which the females, but not males, need to locate and remember potential host nests, have found that females out-perform males in some spatial learning tasks, but not others, further suggesting that individual differences in spatial ability may depend on task design and scale of spatial location (Sherry & Guigueno, 2019). This limitation mirrors the more general problem in evolutionary ecological studies of cognition where there is often a lack of a clear link between standardised cognitive tests (e.g.…”
Section: Spatial Learning Speedmentioning
confidence: 99%
“…For example, a current focus of research in food caching species is to measure spatial learning under standardised conditions, usually on a small scale, to infer performance in cache retrieval at a larger spatial scale, or to predict fitness, but it remains unclear whether observed associations relate to navigation through the environment or cache retrieval at a fine spatial scale (Healy, 2019;Healy et al, 2005Healy et al, , 2009Krebs et al, 1990;McGregor & Healy, 1999). Similarly, work on parasitic cowbirds in which the females, but not males, need to locate and remember potential host nests, have found that females out-perform males in some spatial learning tasks, but not others, further suggesting that individual differences in spatial ability may depend on task design and scale of spatial location (Sherry & Guigueno, 2019). This limitation mirrors the more general problem in evolutionary ecological studies of cognition where there is often a lack of a clear link between standardised cognitive tests (e.g.…”
Section: Spatial Learning Speedmentioning
confidence: 99%
“…Her mate very much leaves her to it. Sherry and Guigeno (2019) found that female brown-headed cowbirds outperformed conspecific males in 1 spatial task but not another and that females had greater hippocampal neurogenesis than did males, a sex difference not seen in red-winged blackbirds, Agelaius phoeniceus, a closely related species that is not a brood parasite. An association between neural data and performance on one apparently spatial task but on not another causes us to examine more closely what ability the animal might actually use to perform well in tests we assume assess a particular cognitive ability (for Sherry & Guigeno, spatial memory).…”
Section: Animal Cognitionmentioning
confidence: 83%
“…For example, a current focus of research in food caching species is to measure spatial cognition under standardized conditions, usually on a small scale, to infer performance in cache retrieval at a larger spatial scale, but it remains unclear whether observed associations relate to navigation through the environment, or cache retrieval at a fine spatial scale (Healy, 2019;Healy et al, 2005Healy et al, , 2009Krebs et al, 1990;McGregor & Healy, 1999). Similarly, work on parasitic cowbirds in which the females, but not males, need to locate and remember potential host nests, have found that females outperform males in some spatial cognition tasks, but not others, further suggesting that individual differences in spatial ability may depend on task design and scale of spatial location (Sherry & Guigueno, 2019). This limitation mirrors the more general problem in evolutionary ecological studies of cognition, where there is often a lack of a clear link between standardized cognitive tests (e.g., problem solving) and functional behavior (innovative foraging) under natural conditions (Morand-Ferron et al, 2016;Rowe & Healy, 2014a, b;Thornton et al, 2014).…”
Section: Figurementioning
confidence: 99%